Reframing Holistic Islamic Education: An Integrative Reading of Syed Muhammad Naquib al-Attas and Ki Hadjar Dewantara - Fadil, Muhammad; Suwendi; Syukur, Taufik Abdillah; Binti Hussin, Zaharah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study develops an integrative framework for holistic Islamic education by comparatively analyzing Syed Muhammad Naquib al-Attas's concept of ta'dib and Ki Hadjar Dewantara's among guidance system. Using qualitative library research, the study examined foundational texts and recent scholarship through thematic coding of educational ontology, epistemology, axiology, pedagogy, and socio-cultural context. The findings show that al-Attas contributes a spiritual-epistemic orientation in which education orders knowledge, action, and character through adab. Dewantara contributes a humanistic-cultural pedagogy centred on guided freedom, the balanced development of cipta, rasa, and karsa, and collaboration among family, school, and community. Their convergence supports a Ta'dib-Among Holistic Islamic Education Framework that links transcendental purpose, learner agency, and culturally grounded educational practice. The framework's novelty lies in treating adab not only as moral content and the among system not only as a teaching method, but as mutually reinforcing foundations for curriculum, teacher practice, and educational ecosystems. This synthesis offers a contextually Indonesian yet internationally legible contribution to Islamic pedagogy, transformative learning, and inclusive character formation.